Positive electrode for lithium secondary battery and method for producing same
By controlling the pore volume and surface area of the positive electrode in lithium secondary batteries, the issue of particle cracking is mitigated, enhancing the battery's performance and reducing gas generation.
Patent Information
- Application Number
- JP2024539988
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-01-11
- Filing Date
- 2023-01-11
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-01-11
AI Technical Summary
Lithium secondary batteries face issues with particle cracking and internal cracks in the positive electrode active material due to excessive rolling, leading to increased contact area with the electrolyte, gas generation, and reduced life characteristics.
A positive electrode with a specific pore volume range of 7.0×10^-3 cm^3/g to 8.0×10^-3 cm^3 and a BET specific surface area of 1.30 m^2/g to 1.50 m^2/g is manufactured by coating a current collector with a positive electrode slurry and controlling the rolling process to minimize particle cracking and ensure optimal contact between particles.
The solution improves initial capacity, life characteristics, and reduces gas generation in lithium secondary batteries by maintaining the integrity of the positive electrode active material.
Smart Images

Figure 2025501316000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2022-0004160 filed on January 11, 2022 and Korean Patent Application No. 10-2023-0003975 filed on January 11, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a positive electrode for a lithium secondary battery having excellent electrochemical properties and a method for producing the same. [Background technology]
[0003] In general, a lithium secondary battery is composed of a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode and the negative electrode contain active materials capable of intercalating and deintercalating lithium ions, and electrical energy is produced by oxidation and reduction reactions that occur when lithium ions are intercalated and deintercalated in the positive electrode and the negative electrode.
[0004] The positive electrode of a lithium secondary battery is manufactured by applying a positive electrode active material to a current collector, rolling it, and then drying it. In recent years, there has been an increasing demand for lithium secondary batteries with high energy density per unit volume so that they can be used in electric vehicles, etc. However, excessive rolling to increase the energy density not only tends to cause particle cracking of the positive electrode active material, but also causes cracks inside the particles.
[0005] If particle breakage or cracks occur in the positive electrode active material, the contact area with the electrolyte increases, which increases the amount of gas generated due to side reactions with the electrolyte and accelerates the deterioration of the active material, which can reduce the battery's life characteristics.
[0006] Therefore, there is a need to develop a method for distinguishing a positive electrode having an optimal rolling condition that has less occurrence of particle breakage and cracks and can exhibit excellent electrochemical properties when applied to a battery. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention provides a positive electrode having excellent electrochemical properties and little damage to the particle structure even after rolling, and a method for producing the same. [Means for solving the problem]
[0008] The present invention relates to a positive electrode current collector; and a positive electrode active material layer formed on at least one surface of the positive electrode current collector and including a positive electrode active material, The positive electrode active material layer is Pore volume is 7.0×10 -3 cm 3 / g~8.0×10 -3 cm 3 / g.
[0009] The present invention also provides a method for producing a semiconductor device comprising the steps of: forming a positive electrode active material layer by coating at least one surface of a positive electrode current collector with a positive electrode slurry containing a positive electrode active material; rolling the positive electrode current collector and the positive electrode active material layer; The pore volume of the positive electrode active material layer after rolling is 7.0×10 -3 cm 3 / g~8.0×10 -3 cm 3 The present invention provides a method for producing a positive electrode for a lithium secondary battery, in which the electrode has a molecular weight of 1000 to 10000 kcal / g. Effect of the Invention
[0010] The positive electrode according to an embodiment of the present invention includes a positive electrode active material with less occurrence of particle cracks and internal cracks, and therefore, when applied to a lithium secondary battery, the initial capacity, life characteristics, and gas generation rate can be improved. [Brief description of the drawings]
[0011] [Figure 1] 1A and 1B are cross-sectional views of a positive electrode before and after rolling, observed with a scanning electron microscope. [Diagram 2]1 shows the results of analyzing the positive electrodes prepared in the examples and comparative examples of the present invention by a Barrett-Joyner-Halenda (BJH) method. [Diagram 3] FIG. 2 is a graph showing the capacity retention rate and the resistance increase rate measured while charging and discharging the batteries using the positive electrodes produced in the examples and comparative examples of the present invention 600 times. [Figure 4] FIG. 13 is a graph showing the results of measuring the amount of gas generated after high-temperature storage for batteries using positive electrodes manufactured in Examples and Comparative Examples of the present invention. [Diagram 5] FIG. 13 is a graph showing the results of measuring the rolling density according to the mixture weight ratio of small particles and large particles in a positive electrode material having a bimodal particle size distribution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will now be described in more detail to aid in understanding the invention. In the present invention, the term "primary particle" refers to a particle unit that is composed of multiple determinants and has no grain boundaries when observed at a magnification of 5,000 to 20,000 times using a scanning electron microscope. The term "average particle size of primary particles" refers to the arithmetic average value calculated after measuring the particle sizes of primary particles observed in a scanning electron microscope image. In the present invention, the "secondary particles" are particles formed by agglomeration of a plurality of primary particles.
[0013] In the present invention, "D 50 " means the particle size at 50% of the volume cumulative particle size distribution of the lithium composite transition metal oxide powder or the positive electrode active material powder, and in the case where the lithium composite transition metal oxide is a secondary particle, the D 50 The above D 50can be measured using the laser diffraction method. For example, after dispersing the lithium composite transition metal oxide powder or the positive electrode active material powder in a dispersion medium, it is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and then a graph of the volume cumulative particle size distribution is obtained, and the size of the particles corresponding to 50% of the volume cumulative amount is obtained.
[0014] In the present invention, the "BET specific surface area" and "pore volume" are calculated from a nitrogen adsorption isotherm in a liquid nitrogen atmosphere at 77K obtained using BELSORP-MAX (MicrotracBEL corp.), the specific surface area is calculated by the BET (Brunauer-Emmett-Teller) multipoint method, and the pore volume is calculated using a BJH (Barrett-Joyner-Halenda) plot for pores with diameters of 2 nm to 185 nm.
[0015] positive electrode First, the positive electrode for a lithium secondary battery according to the present invention will be described. In order to achieve high energy density in lithium secondary batteries and to ensure high electrical conductivity through contact between the current collector and the active material, it is advantageous to manufacture electrodes with high rolling density. However, as can be seen from Figure 1, which shows the surface of the electrode before rolling (A) and the surface of the electrode after rolling (B) observed with a scanning electron microscope (SEM), not only is it easy for particle cracks to occur, causing the particle shape of the active material to be distorted, but cracks can also occur inside the particles, depending on the rolling conditions.
[0016] Specifically, if the rolling density is too high, the primary particles of the active material are broken, which can cause the conductive path to be disconnected, or the reaction area with the electrolyte to increase, which can cause gas generation to intensify. Therefore, the electrochemical performance of the electrode and gas generation due to side reactions are greatly affected by the rolling characteristics.
[0017] Therefore, the present inventors have devised a new parameter to enable selection of a positive electrode containing an active material in a good particle state from a positive electrode in a rolled state. Specifically, in a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector and containing a positive electrode active material, the pore volume of the positive electrode active material layer is 7.0×10 -3 cm 3 / g~8.0×10 -3 cm 3 / g, it was confirmed that the cathode active material particles in the optimum state can be contained, which contributes to improving the performance of the battery.
[0018] Specifically, the pore volume of the positive electrode active material layer is 7.0 × 10 -3 cm 3 / g or more, preferably 7.1×10 -3 cm 3 / g or more, the contact between particles is sufficient, the resistance can be reduced, and the capacity of the cell can be increased. -3 cm 3 / g or less, preferably 7.6×10 -3 cm 3 When the average particle size is less than 1 / g, the degree of particle cracking of the active material inside the electrode is small, so that the phenomenon of intensified gas generation inside the cell can be prevented.
[0019] On the other hand, in one embodiment of the present invention, the BET specific surface area of the positive electrode active material layer is 1.30 m 2 / g excess 1.50m 2 / g, preferably less than 1.32m 2 / g~1.48m 2 / g, more preferably 1.33m 2 / g~1.45m 2 / g. In this case, the particle cracking of the active material inside the electrode is not excessive and the contact between the particles is sufficient, so that the resistance characteristics can be improved.
[0020] In one embodiment of the present invention, the positive electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, aluminum; stainless steel; nickel; titanium; calcined carbon; or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like may be used.
[0021] Meanwhile, the positive electrode active material is not particularly limited as long as it is a compound capable of reversible intercalation and deintercalation of lithium, and may include, for example, any one or more selected from the group consisting of lithium composite transition metal oxides including lithium cobalt-based oxides, lithium nickel-based oxides, lithium nickel cobalt-based oxides, lithium manganese-based oxides, lithium nickel manganese-based oxides, lithium phosphate-based oxides, and lithium nickel cobalt manganese-based oxides.
[0022] Specifically, the positive electrode active material is LiCoO 2 Lithium cobalt oxides such as (LCO); LiNiO 2 Lithium nickel oxides such as (LNO); LiNi 1-y4 Co y4 O 2 Lithium nickel cobalt oxides such as (0≦y4<1); LiMnO 2 (LMO), LiMnO 3 , LiMn 2 O 3 , and Li 2 MnO 3 Lithium manganese oxides such as Li 1+y1 Mn 2-y1 O 4 (0≦y1≦0.33), LiNi y2 Mn 2-y2 O 4 (0≦y2≦2), LiNi y3 Mn 2-y3 O 2 (0.01≦y3≦0.1), and Li 2 NiMn 3 O 8 Lithium nickel manganese oxides such as LiFePO 4and LiCoPO 4 such as lithium phosphate-based oxides; and any one or more selected from the group consisting of lithium nickel cobalt manganese-based oxides represented by the following Chemical Formula 1 may be included.
[0023] In one embodiment of the present invention, the positive electrode active material may include a lithium composite transition metal oxide represented by the following Chemical Formula 1.
[0024] [Chemical Formula 1] Li 1+x (Ni a Co b Mn c M d )O 2
[0025] In the Chemical Formula 1, M is any one or more selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, x, a, b, c, and d are respectively -0.2 ≦ x ≦ 0.2, 0.50 ≦ a < 1, 0 < b ≦ 0.25, 0 < c ≦ 0.25, 0 ≦ d ≦ 0.1, and a + b + c + d = 1.
[0026] Further, the positive electrode active material may include a lithium composite transition metal oxide containing 70 mol% or more of nickel with respect to the total mol of transition metals. Specifically, in the Chemical Formula 1, a lithium composite transition metal oxide in which a, b, c, and d are respectively 0.70 ≦ a < 1, 0 < b ≦ 0.20, 0 < c ≦ 0.20, and 0 ≦ d ≦ 0.05 may be included. More specifically, a lithium composite transition metal oxide in which a, b, c, and d are respectively 0.80 ≦ a < 1, 0 < b ≦ 0.15, 0 < c ≦ 0.15, and 0 ≦ d ≦ 0.03 may be included.
[0027] In one embodiment of the present invention, the positive electrode active material is Li(Ni 0.83 Co 0.05 Mn 0.10 Al 0.02 )O 2and Li(Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 )O 2 may be one or more selected from the above.
[0028] The positive electrode active material is D 50 The positive electrode active material may contain a small particle positive electrode active material and a large particle positive electrode active material having different sizes, in which case the rolling characteristics of the electrode can be improved. At this time, the D of the small particle positive electrode active material 50 may be 2 μm to 5 μm, and D of the large particle positive electrode active material may be 50 may be 8 μm to 12 μm.
[0029] In one embodiment of the present invention, the weight ratio of the small particles to the large particles (i.e., weight of the small particle positive electrode active material / weight of the large particle positive electrode active material) may be 1.0 to 2.0, preferably 1.2 to 1.8, and more preferably 1.5. Mixing at such a weight ratio is advantageous for achieving a high rolling density under various pressure conditions.
[0030] In one embodiment of the present invention, the positive electrode active material layer may have a porosity of 20% to 25%, where the porosity is a value calculated by the following [Equation 1].
[0031] [Formula 1] Porosity of positive electrode active material layer (%)=((true density of positive electrode active material−electrode density) / true density of positive electrode active material)×100 The electrode density in the above formula 1 is a value calculated by the following formula 2.
[0032] [Formula 2] Electrode density = (weight of positive electrode - weight of positive electrode current collector) / (a x b x c) In the above formula 2, a, b, and c are the width, length, and height, respectively, measured after separating the positive electrode current collector from the positive electrode.
[0033] In one embodiment of the present invention, the thickness of the positive electrode active material layer may vary depending on the amount of the positive electrode slurry applied, and may be, for example, 50 μm to 54 μm, preferably 51 μm to 53 μm, and the total thickness of the positive electrode including the thickness of the positive electrode current collector may be 60 μm to 100 μm. In this case, there is an advantage that it is advantageous for improving the energy density and controlling the drying process. The thickness of the positive electrode is measured in a state where the positive electrode is stretched to the maximum and flattened.
[0034] Positive electrode manufacturing method Next, a method for producing the positive electrode for a lithium secondary battery will be described. A method for producing a positive electrode for a lithium secondary battery according to the present invention includes the steps of: coating at least one surface of a positive electrode current collector with a positive electrode slurry containing a positive electrode active material to form a positive electrode active material layer; and rolling the positive electrode current collector and the positive electrode active material layer, wherein the pore volume of the positive electrode active material layer after rolling is 7.0×10 -3 cm 3 / g~8.0×10 -3 cm 3 For each component of the production method, the above-mentioned explanations regarding each component of the positive electrode can be cited.
[0035] In one embodiment of the present invention, the BET specific surface area of the positive electrode active material layer after rolling is 1.30 m 2 / g excess 1.50m 2 / g, preferably less than 1.32m 2 / g~1.48m 2 / g, more preferably 1.33m 2 / g~1.45m 2 / g.
[0036] In one embodiment of the present invention, the coating of the positive electrode slurry is performed by applying the positive electrode slurry to at least one surface of the positive electrode current collector in an amount of 350 mg / 25 cm. 2 ~480mg / 25cm 2 Loading amount of 380mg / 25cm 2 ~460mg / 25cm 2 The coating may be performed using a coating agent.
[0037] In one embodiment of the present invention, the thickness of the positive electrode active material layer after rolling may be 66% to 72%, preferably 68% to 72%, of the thickness of the positive electrode active material layer before rolling. In this case, the BET specific surface area and pore volume of the positive electrode active material can be adjusted to the ranges of the present invention while achieving a suitable rolling density.
[0038] Meanwhile, the positive electrode slurry may further include a binder and / or a conductive material in addition to the positive electrode active material, and may be prepared by dissolving them in a solvent.
[0039] The positive electrode active material may be included in an amount of 80 wt% to 99 wt%, specifically 90 wt% to 99 wt%, based on the total weight of the solid content in the positive electrode slurry. In this case, if the content of the positive electrode active material is 80 wt% or less, the energy density may be reduced, resulting in a reduced capacity.
[0040] The binder is a component that aids in binding between the active material and the conductive material and between the current collector, and may be added in an amount of 1% by weight to 30% by weight based on the total weight of the solid content in the positive electrode slurry. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, or various copolymers thereof.
[0041] The conductive material is a substance that does not induce chemical changes in the battery and imparts conductivity, and may be added in an amount of 0.5% by weight to 20% by weight based on the total weight of the solid content in the positive electrode slurry.
[0042] The conductive material may be selected from conductive materials such as carbon blacks, such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders, such as natural graphite, artificial graphite, carbon nanotubes, and graphite; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives.
[0043] The solvent for the positive electrode slurry may contain an organic solvent such as N-methyl-2-pyrrolidone (NMP) and may be used in an amount that provides a preferred viscosity when containing the positive electrode active material, binder, conductive material, etc. For example, the positive electrode slurry containing the positive electrode active material, binder, and conductive material may be contained so that the solid content concentration is 40% by weight to 90% by weight, preferably 60% by weight to 80% by weight.
[0044] In one embodiment of the present invention, the rolling step may be performed by cutting the positive electrode current collector coated with the positive electrode slurry into a size of 10 cm to 12 cm in width and 3 cm to 4 cm in length, placing the cut piece between two rolling rolls, and compressing the cut piece by adjusting the distance between the rolling rolls.
[0045] Lithium secondary battery Next, the lithium secondary battery according to the present invention will be described. The lithium secondary battery of the present invention includes the positive electrode according to the present invention described above, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and may be manufactured by a method for manufacturing a typical lithium secondary battery, except for using the positive electrode according to the present invention.
[0046] Meanwhile, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0047] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector. The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 to 500 μm, and may have fine irregularities formed on the surface of the current collector to strengthen the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0048] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material. The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), SnO 2 , metal oxides that can be doped and dedoped with lithium, such as vanadium oxide and lithium vanadium oxide; or composites containing the metallic compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, and any one or a mixture of two or more of these may be used.
[0049] Also, a metallic lithium thin film may be used as the negative electrode active material. Also, as the carbon material, either low crystalline carbon or high crystalline carbon may be used. As the low crystalline carbon, soft carbon and hard carbon are representative, and as the high crystalline carbon, amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes are representative.
[0050] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon-based materials such as carbon fibers and carbon nanotubes; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one of these may be used alone or a mixture of two or more of them may be used. The conductive material may be usually contained in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.
[0051] The binder plays a role in improving the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these alone or a mixture of two or more of them may be used. The binder may be included in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.
[0052] The negative electrode active material layer may be manufactured, for example, by applying a negative electrode slurry containing a negative electrode active material, and optionally a binder and a conductive material, onto a negative electrode current collector and drying the applied negative electrode slurry, or by casting the negative electrode slurry onto another support, peeling the negative electrode slurry from the support, and laminating the resulting film onto the negative electrode current collector.
[0053] The solvent for the negative electrode slurry may include water or an organic solvent such as NMP or alcohol, and may be used in an amount that provides a preferred viscosity when the negative electrode active material, binder, conductive material, etc. are contained. For example, the negative electrode active material, binder, and conductive material may be contained so that the solid content concentration in the slurry is 30% by weight to 80% by weight, preferably 40% by weight to 70% by weight.
[0054] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular restrictions, and it is particularly preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.
[0055] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0056] Specifically, the electrolyte may include an organic solvent and a lithium salt. The organic solvent may be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvent that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a C2-C20 linear, branched, or cyclic hydrocarbon group, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant capable of improving the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) is more preferred.
[0057] The lithium salt may be any compound capable of providing lithium ions used in a lithium secondary battery without any particular limitation.6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlO 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 The lithium salt may be used at a concentration within the range of 0.1 to 5.0 M, preferably 0.1 to 3.0 M. When the lithium salt concentration is within the above range, the electrolyte has suitable conductivity and viscosity, and therefore can exhibit excellent electrolyte performance, allowing lithium ions to migrate effectively.
[0058] In addition to the constituents of the electrolyte, the electrolyte may further contain additives for improving the life characteristics of the battery, suppressing the decrease in the battery capacity, improving the discharge capacity of the battery, etc. For example, the additives may be, but are not limited to, haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, which may be used alone or in combination. The additives may be contained in an amount of 0.1 to 10% by weight, preferably 0.1 to 5% by weight, based on the total weight of the electrolyte.
[0059] As described above, the lithium secondary battery including the positive electrode according to the present invention stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs).
[0060] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same. The battery module or battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0061] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, the present invention will be described in detail with reference to the embodiments so that those skilled in the art can easily carry out the present invention. EXAMPLES
[0062] [Examples and Comparative Examples: Production of Positive Electrode] Reference Experiment Example 1. Prior to the manufacture of the positive electrode, in order to confirm the optimal mixing ratio of small particles and large particles, the rolling density value according to the mixing weight ratio of the bimodal positive electrode material was confirmed by the following method.
[0063] Specifically, D 50 Li(Ni 0.83 Co 0.05 Mn 0.10 Al 0.02 )O 2 and D. 50 Li(Ni 0.86 Co 0.5 Mn 0.7 Al0.2 )O 2 (D 50 = 10 μm) in weight ratios of 7:3, 6:4, 5:5, 4:6, and 3:7, respectively, to produce positive electrode materials having bimodal particle size distributions.
[0064] The rolling density of each of the prepared cathode materials was measured using HPRM-1000. Specifically, 5 g of the cathode materials prepared at each weight ratio was placed in a cylindrical mold, and the mold containing each cathode material was pressurized at 2 tons. The height of the pressurized mold was then measured with a Vernier caliper to obtain the rolling density. The rolling density was obtained in the same manner when the pressure applied to the mold was changed to 5 tons and 9 tons, and the results are shown in Figure 5.
[0065] From the results of FIG. 5, it can be seen that the rolling density is highest when the mixing weight ratio of small particles to large particles is 6:4 under all pressure conditions of 2 tons, 5 tons, and 9 tons. Therefore, in the following examples, the cathode material was manufactured by applying this weight ratio.
[0066] Comparative Example 1 D 50 Li(Ni 0.83 Co 0.05 Mn 0.10 Al 0.02 )O 2 and D. 50 Li(Ni 0.86 Co 0.5 Mn 0.7 Al 0.2 )O 2 (D 50 = 10 μm) were mixed in a weight ratio of 6:4 to produce a bimodal cathode material.
[0067] The positive electrode material, conductive material (carbon black), and binder (polyvinylidene fluoride, PVdF) were mixed in a weight ratio of 97.5:1.0:1.5 in N-methyl-2-pyrrolidone (NMP) solvent to prepare a positive electrode slurry (solid content: 76 wt%). The true density of the positive electrode active material was 4.475 g / cc.
[0068] The positive electrode slurry was applied to one side of an aluminum current collector and then dried at 130° C. with a loading of 450 g / 25 cm 2 An electrode including the active material layer was manufactured. In this case, the thickness of the active material layer was 75 μm. After cutting to 11 cm × 3.5 cm, it was placed between two rolling rolls and the gap between the rolling rolls was adjusted at 25 ° C., and a positive electrode with an active material layer thickness and porosity of 70 μm and 42.5%, respectively, was manufactured.
[0069] Comparative Example 2 In Comparative Example 1, a positive electrode was prepared in the same manner as in Example 1, except that the active material layer was rolled to have a thickness of 55 μm and a porosity of 26.8%, respectively.
[0070] Comparative Example 3. In Comparative Example 1, a positive electrode was prepared in the same manner as in Example 1, except that the active material layer was rolled to have a thickness of 49 μm and a porosity of 17.8%, respectively.
[0071] Example 1. In Comparative Example 1, a positive electrode was prepared in the same manner as in Example 1, except that the active material layer was rolled to have a thickness of 53 μm and a porosity of 24.0%, respectively.
[0072] Example 2. In Comparative Example 1, a positive electrode was prepared in the same manner as in Example 1, except that the active material layer was rolled to have a thickness of 51 μm and a porosity of 21.1%.
[0073] [Experimental Example 1: Measurement of BET specific surface area and pore volume] The positive electrodes of Comparative Examples 1 to 3 and Examples 1 and 2 prepared above were cut into pieces with an area of 1.96 cm x 1.96 cm, and samples were taken from each positive electrode so that the total weight of the positive electrode was 3.5 g or more, and the samples were placed in a BELSORP-MAX (MicrotracBEL corp.). Then, the BET (Brunauer-Emmett-Teller) specific surface area of the positive electrode active material layer was confirmed by subtracting the weight of the current collector, and the pore volume was confirmed by a BJH (Barrett-Joyner-Halenda) plot. The BJH plot was obtained for pores with diameters of 2 nm to 185 nm, and is shown in FIG. 2, and the pore volume values calculated therefrom are shown in Table 1 below.
[0074] [Table 1]
[0075] [Experimental Example 2: Evaluation of battery performance] (1) Initial capacity evaluation An electrode assembly was prepared by interposing a porous polyethylene separator between each of the positive electrodes and lithium metal negative electrodes prepared in Examples 1 and 2 and Comparative Examples 1 to 3, and then the electrode assembly was placed inside a battery case. An electrolyte was then injected into the case to prepare a coin half cell lithium secondary battery. The electrolyte was prepared by mixing ethylene carbonate / dimethyl carbonate / diethyl carbonate in a volume ratio of 3:4:3 with 1M concentration of LiPF 6 The manufactured coin half cells were activated and then charged / discharged once at room temperature (25°C) at a charge / discharge rate of 0.1C / 0.1C. The capacity after one charge / discharge was taken as the initial capacity and is shown in Table 2 below.
[0076] (2) Evaluation of life characteristics Lithium secondary batteries using the positive electrodes of Examples 1 and 2 and Comparative Examples 2 and 3 were manufactured in the same manner as in the coin half-cell, except that the negative electrode prepared as follows was used instead of the lithium metal negative electrode.
[0077] The graphite (a mixture of artificial graphite and natural graphite in a weight ratio of 8:2) as the negative electrode active material, styrene-butadiene rubber (SBR) as the binder, and carbon black as the conductive material were mixed in a weight ratio of 97.6:0.8:1.6, and then added to water as the solvent to prepare a negative electrode mixture slurry. The negative electrode mixture slurry was applied to a copper (Cu) thin film as a negative electrode current collector with a thickness of 10 μm, dried to prepare a negative electrode, and then roll pressed to prepare a negative electrode.
[0078] The lithium secondary batteries thus manufactured were subjected to an activation process at 25°C and a rate of 0.1C, and then the gas in the batteries was removed by a degassing process. The lithium secondary batteries from which the gas had been removed were subjected to constant current / constant voltage (CC / CV) charging at a rate of 0.33C up to 4.2V and 0.05C cut-off charging at a temperature of 25°C, and constant current (CC) discharging at a rate of 0.33C up to 2.5V.
[0079] Each of the above charge / discharge cycles was counted as one cycle, and the discharge capacity in the initial state (one cycle) was measured using a PNE-0506 charger / discharger (manufacturer: PNE solution, Inc., 5 V, 6 A). The results are shown in Table 2 below as the initial capacity.
[0080] Thereafter, the same charge / discharge cycle was repeated 600 times, and the discharge capacity retention rate was measured. The results are shown in FIG. 3. The retention rate after 600 charge / discharge cycles was calculated based on the initial capacity, and shown in Table 2 below as the capacity retention rate.
[0081] In addition, after charging to 50% SOC at 25° C., a discharge pulse of 1C was applied for 10 seconds, and the DC-iR was calculated from the voltage drop. The results are shown in FIG. 3. The resistance increase rate after 600 charge / discharge cycles with respect to the initial resistance was calculated and shown in Table 2 below.
[0082] (3) Measurement of volume change Lithium secondary batteries were manufactured using the positive electrodes of Examples 1 and 2 and Comparative Examples 2 and 3 in the same manner as described in the evaluation section of life characteristics, and an activation process was performed at 25° C. and 0.2C rate, and then gas in the battery was removed by a degassing process. Then, at room temperature (25° C.), charging was performed at 0.33C rate up to 4.2V under constant current / constant voltage conditions, 0.05C cut-off charging, and discharging at 0.33C 2.5V.
[0083] Then, the battery was fully charged under the same conditions as above until the SOC reached 100%. The volume of the fully charged battery was measured at room temperature using the buoyancy method, and this was taken as the initial volume.
[0084] The batteries after volume measurement were stored at 60°C for 16 weeks, and the amount of gas generated was measured according to the volume change in the following manner, and the results are shown in Figure 4. After each volume measurement, the batteries were transferred to a charger at room temperature (25°C) and charged at a rate of 0.33C under constant current / constant voltage conditions up to 4.2V and 0.05C cut-off charging, and then fully charged again to 100% SOC. The volume of the fully charged batteries was measured at room temperature using a buoyancy method, and the batteries were stored again at 60°C. The difference between the volume measured after 16 weeks of storage and the initial volume was calculated and reported as the amount of gas generated in Table 2 below.
[0085] [Table 2]
[0086] From the results in Table 2, it can be seen that the batteries manufactured using the positive electrodes of Examples 1 and 2 in which the positive electrode active material layer satisfies the pore volume range of the present invention exhibited consistently excellent initial capacity, capacity retention rate, resistance increase rate, and gas generation amount.
[0087] Specifically, the pore volume of the positive electrode active material layer is 7.0 × 10 -3 cm 3 In the case of Comparative Examples 1 and 2 using positive electrodes with a pore volume of less than 8.0×10 -3 cm 3 It can be seen that in the case of Comparative Example 3 using a positive electrode having a capacity exceeding 100% by mass / g, the amount of gas generated is significantly increased.
Claims
1. a positive electrode current collector; and a positive electrode active material layer formed on at least one surface of the positive electrode current collector and including a positive electrode active material, The positive electrode active material layer has a pore volume of 7.0×10 -3 cm 3 / g to 8.0 x 10 -3 cm 3 / g.
2. The positive electrode active material layer has a BET specific surface area of 1.30 m 2 / g excess 1.50m 2 The positive electrode for a lithium secondary battery according to claim 1 , wherein the Mo content is less than 1 / g.
3. The positive electrode active material is D 50 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the positive electrode particles include different small particle positive electrode active material and large particle positive electrode active material.
4. D of the small particle positive electrode active material 50 The positive electrode for a lithium secondary battery according to claim 3, wherein the thickness is 2 μm to 5 μm.
5. D of the large particle positive electrode active material 50 The positive electrode for a lithium secondary battery according to claim 3, wherein the thickness is 8 μm to 12 μm.
6. 4. The positive electrode for a lithium secondary battery according to claim 3, wherein a weight ratio of the small particle positive electrode active material to the large particle positive electrode active material is 1.0 to 2.
0.
7. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the positive electrode active material comprises a lithium composite transition metal oxide represented by the following Chemical Formula 1: [Chemical formula 1] Li 1+x (N a Co b Mn c M d )O 2 In the above Chemical Formula 1, M is at least one selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, a, b, c, and d are -0.2≦x≦0.2, 0.50≦a<1, 0<b≦0.25, 0<c≦0.25, 0≦d≦0.1, and a+b+c+d=1, respectively.
8. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the positive electrode active material comprises a lithium composite transition metal oxide containing 70 mol % or more of nickel based on the total moles of the transition metals.
9. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the positive electrode active material layer has a porosity of 20% to 25%.
10. forming a positive electrode active material layer by coating at least one surface of a positive electrode current collector with a positive electrode slurry containing a positive electrode active material; rolling the positive electrode current collector and the positive electrode active material layer; The pore volume of the positive electrode active material layer after rolling is 7.0×10 -3 cm 3 / g to 8.0 x 10 -3 cm 3 / g.
11. The BET specific surface area of the positive electrode active material layer after rolling is 1.30 m 2 / g excess 1.50m 2 The method for producing a positive electrode for a lithium secondary battery according to claim 10, wherein the Mo content is less than 1 / g.
12. The coating of the positive electrode slurry was performed by applying the positive electrode slurry to at least one surface of the positive electrode current collector in an amount of 350 mg / 25 cm. 2 ~480mg / 25cm 2 The method for producing a positive electrode for a lithium secondary battery according to claim 10, wherein the coating is performed with a loading amount of
13. The method for producing a positive electrode for a lithium secondary battery according to claim 10, wherein the thickness of the positive electrode active material layer after rolling is 66% to 72% of the thickness of the positive electrode active material layer before rolling.
14. A lithium secondary battery comprising: the positive electrode for a lithium secondary battery according to claim 1; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.
Citation Information
Patent Citations
Lithium secondary battery
JP2012216500A
Positive electrode active material for lithium secondary battery, and lithium secondary battery
JP2014032803A
Method for manufacturing electrode active material slurry for nonaqueous electrolyte secondary batteries
JP2015072784A